Algebra 2 is a more advanced level of algebra 1 where you will learn about polynomials, quadratic expressions, trigonometry and more. Algebra 2 is simpler if you've got a good grasp on algebra 1 and pre algebra basics but if you don't, then worry not. Algebra 2 solver is an online resource that you can use to upgrade your algebra skills right from home. Algebra 2 solvers assign math helpers to each student, ensuring individual attention and the freedom to learn at your own pace. Students schedule sessions themselves, whenever they want. So you can learn algebra 2 online once a month, once a week or every day, depending on how much help you want.

## Free Algebra 2 Solver

### Solved Examples

**Question 1:**Solve $\frac{x^3 - x}{2x}$

**Solution:**

Given $\frac{x^3 - x}{2x}$

Solve for x,

$\frac{x^3 - x}{2x}$ = $\frac{x(x^2 - 1)}{2x}$

= $\frac{x^2 - 1}{2}$

= $\frac{(x + 1)(x - 1)}{2}$

[ a

=> $\frac{x^3 - x}{2x}$ = $\frac{(x + 1)(x - 1)}{2}$

Solve for x,

$\frac{x^3 - x}{2x}$ = $\frac{x(x^2 - 1)}{2x}$

= $\frac{x^2 - 1}{2}$

= $\frac{(x + 1)(x - 1)}{2}$

[ a

^{2}- b^{2}= (a - b)(a + b) ]=> $\frac{x^3 - x}{2x}$ = $\frac{(x + 1)(x - 1)}{2}$

**Question 2:**Solve (4 + 2i)(5 - 3i)

**Solution:**

Given (4 + 2i)(5 - 3i)

(4 + 2i)(5 - 3i) = 4(5 - 3i) + 2i(5 - 3i)

= 4 * 5 - 4 * 3i + 2i * 5 - 2i * 3i

= 20 - 12i + 10i - 6i

[ i

= 20 - 2i + 6

= 26 - 2i

=> (4 + 2i)(5 - 3i) = 26 - 2i

(4 + 2i)(5 - 3i) = 4(5 - 3i) + 2i(5 - 3i)

= 4 * 5 - 4 * 3i + 2i * 5 - 2i * 3i

= 20 - 12i + 10i - 6i

^{2}[ i

^{2}= - 1 ]= 20 - 2i + 6

= 26 - 2i

=> (4 + 2i)(5 - 3i) = 26 - 2i

**Question 3:**Solve system of equations

2x + y = 5 and x - y = 1

**Solution:**

**Step 1:**

Given system of linear equations

2x + y = 5 ...................................(1)

x - y = 1 .....................................(2)

Step 2:

Step 2:

Solve equation (1) and equation (2)

Add (1) and (2), to eliminate the coefficient of y.

=>

2x + y = 5

+ x - y = 1

------------------

3x + 0 = 6

------------------

=> 3x = 6

Divide each side by 3

=> $\frac{3x}{3} = \frac{6}{3}$

=> x = 2

Step 3:

Step 3:

Put x = 2 in equation (2), to find the value of y.

=> 2 - y = 1

Subtract 2 from both sides

=> 2 - y - 2 = 1 - 2

=> - y = - 1

or y = 1

Hence, the solution of the system is (x, y) = (2, 1).